EVALUASI PROSES PENYUSUNAN ANGGARAN BERBASIS KINERJA PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN NAGEKEO - Nuba, Natalia Reinandi; Banda, Falentina Lucia; Soleiman, Iriany Dewi (Program Studi Akuntansi Universitas Flores, 2024)
This research aims (1) to determine the process of preparing performance-based budgets at the One Stop Integrated Services and Investment Service in Nagekeo Regency. (2) to find out the evaluation of the performance-based budget preparation process at the Nagekeo Regency Investment and One-Stop Integrated Services Service. (3) to determine the obstacles and efforts to overcome problems in the performance-based budget preparation process at the Nagekeo Regency Investment and One-Stop Integrated Services Service. This research is descriptive research. Data was collected by observation, interviews, documentation and literature study using qualitative descriptive analysis techniques. The results of this research show that the process of preparing a performance-based budget at the Nagekeo Regency Investment and One-Stop Integrated Services Service uses main performance indicators that can be understood by all employees. The Department applies six dimensions regarding evaluation, namely: effectiveness, efficiency, adequacy, alignment, responsiveness and accuracy. In its implementation, there were obstacles, namely delays in preparing and changing regional income and expenditure budgets, cheapness in determining unit price standards, lack of accuracy in preparing budget disbursement plans and limited budgets. The efforts made are to always try to update prices at least twice a year to determine standard unit prices. Budget achievement targets and budget determination are carried out at the beginning or middle of the year so that program realization is carried out optimally, there is commitment and trust with third parties when carrying out procurement, efforts to meet community needs optimally and respond quickly if there are complaints submitted by the community.